Book Review : NEUROTRAUMA AND CRITICAL CARE OF THE BRAIN - Septian Dewi Periska (Berkala Ilmiah Kedokteran Duta Wacana, 2018)
Traumatic Brain Injury (TBI) is one of the leading cause of death and disability. TBI and spinal cord injuries have impacts on patients life, their families and also to the comunity. This edition retained the book structure of the first edition with emphasis in critical care and also it offers review the updated guideline recommendation. A review gives the reader not only summary of the content but also a critical assesment about the content. Additionally, this book gives the reader content about a brief review of a basic ethical framework. The concern is not only about science but also about prehospital care, critical care, outcome, ethical issue, prevention and sosioeconomic.